Dietary intervention with Polygonatum sibiricum polysaccharides mitigates cadmium liver toxicity: a gut-liver axis perspective - Qiannan Di; Huimin Zhou; Huifang Chen; Xiaowei Wang; Xiao Huang (Frontiers in Nutrition)
Cadmium (Cd) contamination in food chains poses a global health threat, necessitating safe and effective dietary interventions. While polysaccharides are emerging as detoxifying agents, the role of Polygonatum sibiricum polysaccharides (PSP) in Cd-induced liver injury remains unexplored. This study established a female rat model of cadmium (Cd)-induced liver toxicity with PSP supplementation (125 mg/kg/day) for 8 weeks. The effect of PSP on Cd-induced hepatotoxicity was evaluated through histopathological assessment, biochemical analysis, and measurements of Cd levels in the liver and kidneys. Metabolomics and gut microbiota analysis further explored the hepatoprotective mechanisms. Results demonstrated that PSP significantly reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in Cd-exposed rats, improved hepatic steatosis, and increased intestinal villi height. PSP decreased Cd accumulation in both the liver and kidney, enhanced intestinal barrier function, promoted the growth of beneficial bacteria (Lactobacillus), and modulated the production of short-chain fatty acids (SCFAs). These effects contribute to the alleviation of Cd-induced hepatic dysfunction and metabolic disorders, including pathways such as riboflavin metabolism, steroid hormone biosynthesis, nucleotide metabolism, purine metabolism, and 2-oxocarboxylic acid metabolism. In conclusion, PSP demonstrates potential as a functional dietary intervention for alleviating Cd-induced hepatotoxicity. This study advocates for PSP as a novel nutraceutical for mitigating dietary Cd toxicity.